Risk factors for strabismus in children born before 32 weeks' gestation. Issue 5 (1st May 1999) - Pennefather, Philippa M; Clarke, Michael P; Strong, Nicholas P; Cottrell, David G; Dutton, Jonathan; Tin, Win
Abstract : AIM: To investigate risk factors associated with strabismus in children born prematurely. METHODS: Prospective study of all children born before 32 weeks' gestation between 1 January 1990 and 31 December 1991 in a geographically defined population of approximately 3 million in the Northern Region of the United Kingdom. All children were examined aged 2 years by the same ophthalmologist and paediatrician. RESULTS: 558 children (98.6% of study group) were examined. Logistic regression showed an increased risk of strabismus in children with cicatricial retinopathy of prematurity (p=0.02), refractive error (p=0.003), family history of strabismus (p<0.0001), and poor neurodevelopmental outcome (p<0.0001), in particular impaired locomotor skills (p=0.008) and hand-eye coordination (p=0.001). Gestational age and regressed acute ROP were not independent risk factors for strabismus (p=0.92 and 0.85 respectively). CONCLUSIONS: This study has identified factors which are independently related to strabismus (although not necessarily causative) and others which are related only indirectly. This may contribute both to the management of children born prematurely and to future studies of the aetiology of strabismus.